1977
DOI: 10.1071/ph770495
|View full text |Cite
|
Sign up to set email alerts
|

Mode Coupling in the Solar Corona. III. Alfvén and Magnetoacoustic Waves

Abstract: Coupling between Alfven waves and fast mode waves obliquely incident on a stratified medium is treated using the method of Clemmow and Heading (1954) within the framework of the cold plasma approximation. A result due to Frisch (1964) is rederived in the special case of vertical incidence. The coupling is strongest for nearly parallel (to the magnetic field lines) propagation, and the coupling ratio may be approximated by Q = (00 /0)" where 0 is the angle between the wave vector and the magnetic field lines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…For most solar atmospheric waves of interest in the chromosphere, we might expect κ to be considerably less than 1, indicating that the Alfvén conversion region can effectively fill the chromosphere; and 2. for φ 90 • , conversion is to outgoing (upward) Alfvén waves, but for φ 90 • conversion predominantly produces backward (downward) propagating Alfvén waves. This was to be expected based on a consideration of whether the fast wave aligns with the magnetic field before or after its reflection, consistent with the finding of Melrose (1977) that fast-to-Alfvén coupling is strongest at small attack angle.…”
Section: Fast-to-alfvén Conversionsupporting
confidence: 82%
See 1 more Smart Citation
“…For most solar atmospheric waves of interest in the chromosphere, we might expect κ to be considerably less than 1, indicating that the Alfvén conversion region can effectively fill the chromosphere; and 2. for φ 90 • , conversion is to outgoing (upward) Alfvén waves, but for φ 90 • conversion predominantly produces backward (downward) propagating Alfvén waves. This was to be expected based on a consideration of whether the fast wave aligns with the magnetic field before or after its reflection, consistent with the finding of Melrose (1977) that fast-to-Alfvén coupling is strongest at small attack angle.…”
Section: Fast-to-alfvén Conversionsupporting
confidence: 82%
“…Is there some way that the Alfvén transmission coefficient can be increased? 2 We postulate and explore a novel possibility that the Alfvén waves have not propagated as transverse waves (Alfvén or kink) from the photosphere, but that instead they have been generated by local mode conversion from reflecting fast waves high in the chromosphere (Melrose 1977;Melrose & Simpson 1977;Cally & Goossens 2008;Cally & Hansen 2011;Khomenko & Cally 2012), where low-ionization fraction is not an issue for the 3-6 mHz frequency range of most interest here. It will be shown that this greatly increases Alfvén penetration of the TR, thereby opening up a potentially more fruitful source of coronal Alfvén waves.…”
Section: Motivationmentioning
confidence: 98%
“…FFT power analysis shows that these perturbations undergo damping when propagating from the footpoints to the apex across the frequency range accessible to CoMP. One possible means of damping these waves is through "mode coupling" -a process inherent to transverse (kink) waves propagating in a loop with an inhomogeneous boundary layer and where the (observed) wave damping occurs due to the transfer of the wave energy from the transverse waves generated at the loop footpoint regions into azimuthal Alfvénic waves as they propagate along the loop (e.g., Melrose 1977;Pascoe et al 2010;Hood et al 2013;Pascoe et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It can also be shown that the total energy of the particle propagating in the Alfvén wave field is conserved in the frame of the wave [e.g., Wu et al , 1997]. But when the inhomogeneities are present in the background plasma, this can play a vital role in modifying the initial waveform even in ideal MHD [e.g., Melrose , 1977; Hollweg and Lilliequist , 1978; Wentzel , 1989; Chagelishvili et al , 1996]. Here, we present one such process that leads to the generation of the electric field which has yet attracted no attention.…”
Section: Introductionmentioning
confidence: 99%